INFLUENCE OF THE PORTFOLIO APPROACH ON THE EFFECTIVE USE OF TIME BY STUDENTS OF HIGHER EDUCATION INSTITUTIONS - Fedor V. Grechnikov; Liudmila S. Klentak (National Research Mordova State University, 2016)
Introduction: the paper examines the influence of the portfolio approach on the effective use of training time by contemporary students. This problem is topical due to modernisation of domestic education and the introduction of the new federal state educational standards of higher education, which foresee the intensification of educational process at Institutions of Higher Education. Materials and Methods: based of the analysis of differentiation of students depending on capability for instruction and desire to learn, the paper reveals the potential categories of students requiring a motivational tool, that would enable them to rapidly and effectively acquire general cultural and professional competences. The students of Samara State Aerospace University participated in the experiment. The instruction of students in control groups was carried out traditionally, and in the experimental one - with the application of portfolio approach. Results: upon completion of testing entitled "do you have a feeling of time?" the research into timesaving potential of portfolio approach has revealed, that students in control and experimental groups can be divided into four categories: "overbusy", "in general able to manage their studies well", "able to manage their studies optimally" and "virtually successful". The research showed that students in experimental groups began to manage more in a shorter time, the portion of students of the second and third categories has increased in comparison with the first and the fourth groups. Discussion and Conclusions: as a whole, the findings have practical significance, making it possible to intensify the educational activity of students. The application of portfolio approach during the organisation of the independent work of students changed their attitude to " the value" of time.